Association of Family History of Type 2 Diabetes with Prostate Cancer: A National Cohort Study - Ji, Jianguang; Sundquist, Jan; Sundquist, Kristina (Frontiers in Oncology, 2016)
Background: Personal history of type 2 diabetes mellitus (T2DM) is associated with a lower incidence of prostate cancer, but the underlying mechanisms are largely unknown. We hypothesized that genetic factors that are involved in the development of T2DM might protect again prostate cancer. Methods: We used a few Swedish registers, including the Swedish Multigeneration Register and the Cancer Register, to examine the risk of prostate cancer among men with a family history of T2DM. Standardized incidence ratios (SIRs) were used to calculate the relative risk. Results: The overall risk of prostate cancer among men with a familial history of T2DM was 0.87 (95%CI 0.86-0.89) as compared to matched controls. The risk was even lower for those multiple affected relatives with T2DM, and it was 0.86 for those with two affected relatives and 0.67 for those with three and more affected relatives. Conclusions: Family history of T2DM was associated with a lower incidence of prostate cancer, and the risk was even lower for those with more than one affected relative. Our study strongly suggests that genetic factors or shared familial factors, such as obesity, that contributed to T2DM may protect against prostate cancer.